Teaching English in Bangladeshi Secondary Schools: A Blessing or A Curse? - Farah Amir (English Department FBS UNP, 2022)
This article examines whether teaching English in Bangladeshi secondary schools is a blessing or a curse. The paper seeks to ask soul-searching questions; reiterates the voices and findings of previous scholars and evokes the need to look at the rot within our system in order to engender genuine and practical transformations. It adopts the desk research methodology and mostly draws data from the review of 50 secondary-based sources. The paper argues that the students learning English in Bangladeshi secondary schools are deprived of many essentials that should make them proficient users of the English language, yet they are expected to be effective users of the language in different real life situations; which is challenging. Furthermore, the paper proposes that if there other acknowledged World Englishes, Bangladesh can have a variety of English that accepts and reflects Bengali pronunciations, grammar and meaning. The paper concludes with the question- if other Asian countries, whose native speakers do not use the English language fluently; still develop in geometric progression, can we still tie the teaching of English in our secondary schools and the ability of students (and the rest of the population) communicating fluently in English to Bangladesh’s development?